PELAKSANAAN PENANGANAN PENGIRIMAN BARANG GENERAL CARGO MELALUI UDARA DI PT. ANGKASA PURA KARGO PEKANBARU - Rizkia Insani; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The activity of sending goods or expedition services is increasingly preferred by the community. More and more people use delivery services, so the implementation of timely handling of goods delivery becomes very important to win the competition. In package delivery services, of course, consumers really want satisfying service from package delivery service companies, namely with fast and timely delivery of goods, guaranteed security. This study aims to determine the implementation of the handling of air shipments at PT. Angkasa Pura Kargo Pekanbaru, based on research that has been done in the field, this research uses a qualitative method with a descriptive approach. The research subject is PT. Angkasa Pura Cargo Pekanbaru. data collection is done by using literature, documentation, observation. Interviews and documents. The results of this study indicate that the implementation of handling goods delivery by air has various kinds of SOP obtained, namely: Reservations, Operations, storage of goods, and delivery of goods are carried out in accordance with the SOPs set by the company PT. Angkasa Pura Cargo, so that the goods received by the customer are in good condition and according to the time set. Keywords : Air Cargo, Reservations, Operations, Delivery of Goods.